Implementation (P5) Profile Strengthening Project Pancasila Students Dimensions of Mutual Cooperation at Madrasah Ibtidaiyah - Apriliyah, Mega; Santoso, Gunawan (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: This research aims to evaluate the implementation of the Pancasila Student Profile Strengthening Project (P5) with a focus on the Gotong Royong dimension in class 4 of MI Al-Mujahidin Joglo. This project is designed to strengthen the values of mutual cooperation among students and improve their social skills through project-based activities integrated with the curriculum. Design/methodology/approach: This research method uses a mixed approach, combining direct observation, interviews, surveys and document analysis. Data was collected from students, teachers, and parents to gain insight into project implementation, challenges faced, and impact on students' character development. Findings: The research results showed that the project implementation was successful in increasing students' understanding of the value of mutual cooperation and cooperation skills. However, there are several challenges, such as limited resources, difficulties in collaboration between students, and a lack of consistent support from parents. This research underlines the importance of integrating Pancasila values in learning and the need for support from various parties to optimize project implementation. Recommendations for improvement include increasing training for teachers, providing adequate resources, and involving parents more actively in project activities. It is hoped that these findings can contribute to the development of curriculum and educational practices that focus on strengthening student character in elementary schools. Paper type: Research paper